HUBUNGAN MOTIVASI DENGAN KOMITMEN ORGANISASI (Kasus Pada Karyawan Pada PT.Sucofindo Cabang Dumai) - Astri Lona Putri; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Application of Motivation is critical in determining the success of the company . High or absence of organizational commitment in self- employees are also caused by a leadership style that is applied in a company . If a leader’s motivation according to the situation faced by the company, it will create a more conducive business climate and ultimately the commitment of employees in the company formed even increased . And so the goal can be achieved with good company. The purpose of this research study is to determine the form of motivation applied to the PT.Sucofindo Subdivision Dumai to know how commitment the organization to PT.Sucofindo Subdivision Dumai and to determine the relationship of motivation and organizational commitment onadministration Departement PT.Sucofindo Subdivision Dumai . In analyzing this study used a statistical technique and model used in this study is the Spearman Rank Correlation . Based on the results of the questionnaire data processing obtained results show that there is a strong relationship between motivation and organizational commitment on the PT.Sucofindo Subdivision Dumai, where the calculation results obtained from the correlation coefficient of 0.730 and hypotheses obtained by calculating t table value of 1.708 with df : 25, and α = 0.05, and t value of 5.340 . Thus H0 is rejected and Ha is accepted , this means motivation has a significant relationship with organizational commitment on the PT .Sucofindo Subdivision Dumai .Thus it can be seen that the motivation has sizable relations with the organization's commitment to the PT.Sucofindo Subdivision Dumai. Keywords:Motivation,OrganizationalCommitment,responsibility.